Ammonia Volatilization after Surface Application of Laying‐Hen and Broiler‐Chicken Manures. Issue 6 (1st November 2014) - Miola, Ezequiel C.C.; Rochette, Philippe; Chantigny, Martin H.; Angers, Denis A.; Aita, Celso; Gasser, Marc‐Olivier; Pelster, David E.; Bertrand, Normand
Abstract : Ammonia (NH3 ) losses after field application of animal manure are affected by manure characteristics. The objectives of this study were to quantify NH3 losses from poultry manures obtained from varied handling and storage systems commonly found in eastern Canada and to relate NH3 emissions to manure characteristics. We measured NH3 volatilization using wind tunnels for 22 d after soil‐surface application of seven solid poultry manures originating from farms varying in production type (laying hens and broiler chickens) and in storage duration and conditions. Cumulative emissions (2.7–7.0 g NH3 –N m −2 ) accounted for 13.6 to 35.0% of the total N applied and 51 to 84% (mean, 70%) of the sum of ammoniacal N, urea N, and uric acid N applied (TAUA). On average, 20% of these losses occurred during the first 4.5 h after application for manures that were not dried in the barn shortly after excretion. Production type and storage durations could not explain differences in NH3 volatilization between manures. Volatilization losses were linearly related to manure dry matter and to manure‐derived NH4 + –N, but sources of N changed with time after application. During the first 7 d, variations in total ammoniacal N applied (TANA) among manures explained most of the variations in cumulative NH3 losses ( r 2 = 0.85 after 26 h and 0.92 after 7 d). After a simulated rainfall (5 mm) on Day 7 that stimulated the decomposition of uric acid in manures, TAUA rather than TANA was related to cumulative emissions ( r 2 = 0.77 after 14 and 22 d). Our results indicate that reliable estimates of NH3 volatilization after land spreading of poultry manures should be based not only on TANA but also on NH4 + –N derived from the decomposition of uric acid, that volatilization losses reported in the literature (including the present study) averaged 50% of TAUA, and that estimates for a given situation also need to account for local environmental conditions.